2011
DOI: 10.1177/1933719110385133
|View full text |Cite
|
Sign up to set email alerts
|

Digibind Reverses Inhibition of Cellular Rb+ Uptake Caused by Endogenous Sodium Pump Inhibitors Present in Serum and Placenta of Women with Preeclampsia

Abstract: These studies evidence EDLF in PE serum. Additionally, PE placentas have high EDLF and may represent a source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Previous research by ourselves 27 and others [28][29][30][31][32] had indicated that an SP inhibitor or EDLF exists in placental homogenates, with higher amounts observed in placenta from women having PE. Our initial hypothesis in this study was that the placenta produces such an EDLF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research by ourselves 27 and others [28][29][30][31][32] had indicated that an SP inhibitor or EDLF exists in placental homogenates, with higher amounts observed in placenta from women having PE. Our initial hypothesis in this study was that the placenta produces such an EDLF.…”
Section: Resultsmentioning
confidence: 99%
“…19 Moreover, recent research also points to EDLFs present in both serum and placenta from women with PE being bound and inactivated by Digibind. 27 Because Digibind recognizes and binds the active EDLF found in PE, we developed an RIA using Digibind as the primary antibody. The assay then measures the same EDLFs endogenous to PE women which it would bind and inactivate as part of Digibind therapy.…”
Section: Endogenous Digitalis-like Factor-specific Immunoassay Employing Digibindmentioning
confidence: 99%
“…Anti-digoxin antibodies interact with a broad range of EDLFs ( 114 ) and have been utilized in both experimental animals and man, with some interesting results ( 87 , 88 , 115 , 116 ). Although the commercial preparation used in most of these studies is no longer available, another commercially available preparation of digoxin antibodies (DigiFab ® ) has similar if not identical cross reactivity with EDLF ( 116 118 ). Finally, the ability of individual cardiotonic steroids (CTS) to interfere with the effects of other CTS has added another layer of complexity and suggests another novel approach to the study of and possible therapy of various conditions in which CTS may be involved ( 105 ).…”
Section: Summary In Retrospect and Future Directionsmentioning
confidence: 99%
“…Indeed, there is evidence that EDLFs may participate in preeclampsia [812]. For that reason we excluded women with preeclampsia from the current study.…”
Section: Commentmentioning
confidence: 99%